Implementing inclusive education issues in bridging the policy-practice gap - Watkins, Amanda, active 2016; Meijer, Cor J. W. (International perspectives on inclusive education, 2016)
The volume will provide an examination of issues around how policy for inclusive education can be implemented in practice. In relation to different thematic policy areas considered in each chapter these questions will be considered: What are the main policy issues for inclusive education? What recommendations are there for addressing these issues? What are the difficulties in implementing these recommendations? How can these difficulties be overcome? Overall conclusions will focus on lessons learnt for supporting the implementation of policy for inclusive education and bridging the policy-practice gap.